A Case Report of a 44-Year-Old Woman With Camurati-Englemann Disease: A Case Report. Issue 3 (10th July 2020) - Owhonda, Rebisi A.; Wells, Joel E.; Lloyd, Eric W.; Mumm, Steven; Kimonis, Virginia
Abstract : Case: A 44-year-old woman presented with easy fatigability, diplopia, dizziness, and a 2-year history of pelvic, hip, and lower extremity aching and pain. Radiograph, magnetic resonance imaging, computed tomography, and histopathologic imaging studies were obtained. Hypersclerosis of the affected bones led to the initiation of a sclerotic bone dysplasia workup and sequencing of the transforming growth factor beta 1 gene located on chromosome 19q13 revealed a heterozygous rare missense variant in exon-4, leading to a final diagnosis of Camurati-Engelmann disease (CED). Medical treatment thus far has had a minimal effect on her symptoms, and the patient continues to be followed. Conclusions: This specific mutation has been reported only once previously in a patient with CED. This case report expands the typical phenotype associated with CED in association with the c.667T>C, p.Cys223Arg variant.